Sulphanilic acid as a recyclable bifunctional organocatalyst in the selective conversion of lignocellulosic biomass to 5-HMF. Issue 8 (25th January 2016) - Mirzaei, Hamid M.; Karimi, Babak
Abstract : We herein report an unprecedented integrated process using organic salts as bifunctional organocatalysts under absolutely metal-free conditions for the conversion of a wide range of biomass-derived carbohydrates, cellulose, and even untreated lignocellulose ( e.g. straw and barley husk) into 5-hydroxymethylfurfural (5-HMF). Abstract : We herein report an unprecedented integrated process using organic salts as bifunctional organocatalysts under absolutely metal-free conditions for the conversion of a wide range of biomass-derived carbohydrates, cellulose, and even untreated lignocellulose ( e.g. straw and barley husk) into 5-hydroxymethylfurfural (5-HMF) in a well-known water/MIBK biphasic solvent system.